Religion and Attitude towards Sustainability: An Analysis on the Effects of Individual Religiosity and Church Membership on Value Orientation - Riegel, Ulrich (Journal of empirical theology, 2023)
Climate change and sustainable lifestyles are discussed intensely in civil society, again. Unlike in the the 1970s and 1980s, however, religious communities seem to play a minor role in this discussion. This raises the question of the importance of religion in regard to an ecological attitude. Based on a sample of N = 4131 (former) church members (age: 14 to 89 years – 47% females – 60% with Bachelor-degree of better), this paper analyzes the effect of centrality of religion (as personal indicator in regard of religion) and membership status (as institutional indicator in regard of religion) on values addressing ecology. The findings indicate that church members and religious individuals show a more positive ecological attitude than individuals that did have disaffiliated from church or are not religious. Highly religious respondents, however, are less concerned with ecology than religious ones. Moreover, the effect of membership status is not significant anymore when socio-demographic variables are added as well as when lifestyle is added. The paper will discuss these findings within the framework of the theoretical distinction between ‘old’ and ‘new’ style of political participation.